A Comparative Study of Grade 12 Students’ Motivation for Learning Science and Social Science According to Gender at Escola Secundária 5 De Maio in Dili, Timor-Leste - dos Santos Passos, Alexandrinha; Lynch, Richard (Scholar: Human Sciences, 2017)
In the learning process, motivation is considered as the main component that encourages learning activity and empowers the process of learning to achieve learning goals. Motivation itself includes one’s sense of intrinsic and extrinsic goal orientation, the impression and value of task, control of learning beliefs and self-efficacy for learning and performance. These are essential parts of the Social Cognitive Theory of Motivation for learning. Although the gender gap continues to exist in all aspects of life, in education several studies on motivation for learning showed that the gender gap is gradually decreasing in the learning of science and social science. This research aimed to find out the level of grade 12 students’ motivation for learning science and social science and to investigate that if there was any significant difference according to their gender at Escola Secundária 5 de Maio in Dili, Timor-Leste. The participants were 226 students among 537 students majoring in science and social science. This study utilized a questionnaire as the instrument for data collection and the collected data were analyzed by frequency, percentage, mean, standard deviation, and independent samples t-test. The research findings indicated that the level of students’ motivation for learning science and social science was very high. Also, there was no significant difference between male and female students’ motivation for learning science and social science. The students also showed high average of overall motivation scales. The paper concludes with recommendations for practice and for future research.